Progressive damage analysis of composite structures using higher-order layer-wise elements. (1st June 2020) - Nagaraj, M.H.; Reiner, J.; Vaziri, R.; Carrera, E.; Petrolo, M.
Abstract: The objective of the current work is the development of a numerical framework for the simulation of damage in composite structures using explicit time integration. The progressive damage is described using a Continuum Damage Mechanics (CDM) based material model, CODAM2, in which the damage initiation and progression are modelled using Hashin's failure criteria and crack-band theory, respectively. The structural modelling uses higher-order theories based on the Carrera Unified Formulation (CUF). The current work considers 2D-CUF models where Lagrange polynomials are used to represent the displacement field through the thickness of each ply, resulting in a layer-wise element model. Numerical assessments are performed on coupon-level specimens, and the results are shown to be in good agreement with reference numerical predictions and experimental data, thus verifying the current implementation for progressive tensile damage. The capability of the proposed framework in increasing the polynomial expansion order through the ply thickness, and its influence on the global behaviour of the structure in the damaged state, is demonstrated. The advantages of using higher-order structural models in achieving significant improvements in computational efficiency are highlighted.